Estudio socio-económico en los hogares de los estudiantes del primero, segundo y tercer años e bachillerato del colegio tecnico “Puyango” de la ciudad de Alamor canton Puyango provincia de Loja y su relacion con el rendimiento académico. Año lectivo 2007 – 2008 lineamientos alternativos - Puglla Valverde, Franklin Stalin (2009)
To begin the investigation process and once obtained the approval of the titled project: I "STUDY SOCIO-ECONOMIC IN THE HOMES OF THE STUDENTS OF THE FIRST, SECOND AND THIRD YEARS OF HIGH SCHOOL OF THE TECHNICAL SCHOOL "PUYANGO" OF THE CITY DE ALAMOR CANTON PUYANGO COUNTY DE LOJA AND THEIR RELATIONSHIP WITH THE ACADEMIC YIELD. SCHOOL YEAR 2007 -2008. ALTERNATIVE" LIMITS, you proceeded to the execution of the same one, fulfilling the norms that it establishes the National University of Loja for this type of works. In this investigative work, he/she intended as general objective: To "know the socioeconomic level in the homes of the students of the first, second and third years of high school of the Technical School Puyango of the city of Alamor, Canton Puyango, County of Loja and their relationship with the academic yield. School year 2007-2008." Aware that all investigative work requires of a scientific process, for that that for the literature revision, scientific methods were used as the inductive, deductive; in the field investigation we apply the analytic method; and as technical the observation and the survey were used directed to students, educational and family parents. The process was carried out it in several stages beginning then with a direct poll that allowed to elucidate the problem to be, with the summary of bibliographical information the same one it was sustained to continue with the process of field investigation where the surveys were applied those involved, data with those that the built hypotheses were verified. According to these gathered data that the socioeconomic serious situation for which crosses the country, affects to all the sectors, and especially to the marginal places. Product of this social inequality, many environments of the quality of people's life are affected, and like it is of being expected, the education is also harmed, since the families don't possess the enough resources to provide the youths of all the implements that require for an appropriate formation, what is a restrictive one in the correct learning. 35.71% of the homes of the investigated students, it is sustained so much by the mother and for the father, and in 30% of the same ones these revenues are not enough, being forced the students to get their own mean of sustenance and to work; however, 37.14% of the students, you go with a lot of difficulty the power to continue the university studies since their parents don't have the economic enough capacity to make it. Considering this scenario, you reached the conclusion that the socio-economic level of the homes of the students of first, second and third years of high school of the Technical School "Puyango", has direct relationship with the academic yield of the same ones. Finally they intend alternative limits, with an eye toward giving solution to this serious situation that faces the education of the country, affected in direct form in the crisis for which crosses the country.